2016
DOI: 10.1016/j.jspd.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lowest Instrumented Vertebra Tilt on Radiographic Measurements in Lenke “C” Modifier Curves Undergoing Selective Thoracic Fusion in Adolescent Idiopathic Scoliosis

Abstract: Level III, Therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Ishikawa et al, reported that the final Cobb angle of the thoracolumbar/lumbar curve was significantly correlated with the immediately post-operative LIV tilt [ 26 ]. On the other hand, Skaggs et al, described that LIV tilt was not associated with post-surgical lumbar Cobb angle [ 27 ]. In our study, the Cobb angle of the lumbar curve and the LIV tilt were significantly improved until 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa et al, reported that the final Cobb angle of the thoracolumbar/lumbar curve was significantly correlated with the immediately post-operative LIV tilt [ 26 ]. On the other hand, Skaggs et al, described that LIV tilt was not associated with post-surgical lumbar Cobb angle [ 27 ]. In our study, the Cobb angle of the lumbar curve and the LIV tilt were significantly improved until 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate curve selection and excessive thoracic correction have been identified as the most common etiologies of coronal imbalance [ 4 , 31 , 32 ]. Meanwhile, numerous studies [ 8 , 21 , 31 33 ] have demonstrated improper placement of the LIV is also an independent risk factor. It is also important to realize the heterogeneity of spontaneous compensation of unfused lumbar segments.…”
Section: Discussionmentioning
confidence: 99%
“…Lenke 1 and 2 adolescent idiopathic scoliosis (AIS) accounts for most AIS, but the optimal therapeutic approach for these patients remains controversial [ 1 ]. As posterior selective thoracic fusion (STF) has become the standard surgical treatment of choice [ 2 ], numerous studies have shown that proper STF can accomplish the underlying aim of preventing scoliosis progression while maintaining global balance [ 3 8 ]. In addition, the spontaneous lumbar curve correction (SLCC) can be achieved by correcting the main thoracic curve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies that aimed to identify the appropriate LIV level on preoperative radiographs 1-6 demonstrated that a neutral and stable vertebra was the ideal LIV for preventing distal lumbar coronal curve decompensation. 3,4,7 In Lenke type 1A curves, surgeons may need to obtain maximum reduction of the apical translation of the main thoracic curve and to extend the LIV, at least to the last vertebra touching the central sacral vertical line (CSVL), in order to avoid postoperative distal lumbar coronal curve decompensation. 5 Even after selecting the correct LIV, decompensation can still occur, 8 indicating that other important factors, such as LIV tilt or LIV rotational angle (LIV rotation), should be…”
mentioning
confidence: 99%